2019
DOI: 10.1142/s1793604719300056
|View full text |Cite
|
Sign up to set email alerts
|

Powder aerosol deposition method — novel applications in the field of sensing and energy technology

Abstract: The Aerosol Deposition (AD) method is a dry spray coating process for the production of dense ceramic coatings at room temperature directly from the ceramic raw powder. In order to avoid confusion with liquid aerosol technology, the term powder aerosol deposition (PAD) is introduced here, to highlight that the aerosol consists only of ceramic powder and carrier gas. Especially in the field of functional ceramics, PAD is a promising alternative to conventional sinter-based production processes. This review focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 128 publications
0
35
0
Order By: Relevance
“…[ 11 ] Additionally, Schubert et al recently published a comprehensive review article on PAD films with a focus on functional ceramics in the field of sensing and energy technology. [ 29 ]…”
Section: Powder Aerosol Depositionmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 11 ] Additionally, Schubert et al recently published a comprehensive review article on PAD films with a focus on functional ceramics in the field of sensing and energy technology. [ 29 ]…”
Section: Powder Aerosol Depositionmentioning
confidence: 99%
“…[11] Additionally, Schubert et al recently published a comprehensive review article on PAD films with a focus on functional ceramics in the field of sensing and energy technology. [29] Many new research fields for PAD films emerged in the recent years, like colored luminescent films [73] and more exotic applications like protective films of lunar regolith for the In Situ Resource Utilization (ISRU) mission from the European Space Agency (ESA) [34] or even martian regolith, [74,75] as well as ceramic brushite films for dental brackets. [76] While for these applications, the film properties are already sufficient in their as-deposited state, many other applications with electrical or magnetic functionality exhibit decreased functional properties for PAD films in the as-deposited state.…”
Section: Powder Aerosol Depositionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 1 ] Due to the worldwide development of this process method, different names like aerosol deposition (AD), [ 2 ] vacuum kinetic spray (VKS), [ 3 ] vacuum cold spray (VCS), [ 4 ] granule spray in vacuum (GSV), or nanoparticle deposition system (NPDS) [ 5 ] are used by different research groups. The variety of suitable ceramics ranges from insulator materials like Al 2 O 3, [ 6 ] dielectric materials like BaTiO 3 and Bi 4 Ti 3 O 12 , [ 7 ] solid electrolytes for proton conducting fuel cells like Ba(Zr, Sn, Ce)O 3 , [ 8–10 ] all‐solid‐state battery electrolytes like Li 7 La 3 Zr 2 O 12 , [ 11 ] sensor materials [ 12 ] and lunar regolith [ 13,14 ] for futuristic applications in space to thermoelectric films like CuFeO 2 . [ 15 ] Thermoelectric materials enable the direct emission‐free conversion of thermal to electrical energy and vice versa.…”
Section: Introductionmentioning
confidence: 99%
“…Upon contact with the substrate, the particles break up and form a nanocrystalline layer, which is further densified by subsequent particles due to a room temperature impact consolidation (RTIC) mechanism. [101] Details on the process can, e.g., be found in the reviews of Akedo [101] and Hanft et al [102] For an overview on investigated materials for sensing and energy applications, we refer to the review from Schubert et al [103] and for first commercial applications to the review by Akedo. [104] In a proof-of-concept study, we demonstrated the fabrication of perovskite thin films using PAD in 2016.…”
Section: Dry Powder Aerosol Depositionmentioning
confidence: 99%